Comparable space use by lions between hunting concessions and national parks in West Africa. Issue 5 (30th March 2020) - Mills, Kirby L.; Harissou, Yahou; Gnoumou, Isaac T.; Abdel‐Nasser, Yaye I.; Doamba, Benoit; Harris, Nyeema C.
Abstract: Spatially varied resources and threats govern the persistence of African lions across dynamic protected areas. An important precursor to effective conservation for lions requires assessing trade‐offs in space use due to heterogeneity in habitat, resources and human presence between national parks (NPs) and hunting areas, the dominant land‐use classifications across their range. We conducted a large camera survey in West Africa, encompassing three NPs and 11 hunting concessions (HCs) in Burkina Faso and Niger. This equates to half of the 26, 500‐km 2 transboundary W‐Arly‐Pendjari protected area complex. We combined occupancy and structural equation modelling to disentangle the relative effects of environmental, ecological and anthropogenic variables influencing space use of Critically Endangered lions across 21, 430 trap‐nights from 2016 to 2018. National parks are intended to serve as refuges from human pressures, and thus we expect higher lion occupancy in NPs compared to neighbouring HCs. But because prey availability drove lion occupancy and was comparable between NPs and HCs, lions exhibited no spatial response to management type. Prey availability was primarily influenced by edge effects and natural water availability. Furthermore, water availability and habitat diversity were higher in HCs, possibly outweighing disturbances from higher human occupancy and road density and contributing to comparable lion space use between management types. Synthesis and applications . We found that lions exhibited no avoidance hunting concessions, despite higher human occupancy than in neighbouring national parks. This may be due to the lions' heavy reliance on depleted prey populations and preferred habitat characteristics in hunting concessions. We offer potential management interventions to indirectly influence lion space use, such as enhancing water availability and reducing human disturbance at park edges. Our findings provide insight into lion habitat preferences in a system degraded by human pressures and prey depletion, aiding in the understanding of the management's role in the ecology and conservation of apex predators and hunted species. Abstract : We found that lions exhibited no avoidance hunting concessions, despite higher human occupancy than in neighbouring national parks. This may be due to the lions' heavy reliance on depleted prey populations and preferred habitat characteristics in hunting concessions. We offer potential management interventions to indirectly influence lion space use, such as enhancing water availability and reducing human disturbance at park edges. Our findings provide insight into lion habitat preferences in a system degraded by human pressures and prey depletion, aiding in the understanding of the management's role in the ecology and conservation of apex predators and hunted species.